Dari Lisan ke Tulisan: Eksplorasi Proses Periwayatan dan Kodifikasi Hadis - Muhammad Fikri Hasbulloh; Cindy Fatikasari Ibrahim; Khoirudin Miftah; Maslani Maslani (Al-Bahtsu: Jurnal Penelitian Pendidikan Islam, 2025)
The study of the traces of hadith as a primary source of Islamic teachings is an important topic in the discourse of Islamic scholarship. This research aims to explain the development of hadith through an analysis of the role of the companions in the transmission of the divine revelation in the form of the Prophet Muhammad's (SAW) hadith. The research method used is library research with a descriptive-analytical qualitative approach to analyze data from classical hadith collections (Shahih Bukhari, Shahih Muslim) and works by major scholars (Ibn Hajar, Ibn Taymiyyah). The results show that the role of the companions in hadith transmission began during the life of the Prophet Muhammad (SAW) and continued until the second century of the Hijri calendar. The recording of hadith began during the time of the Prophet (SAW), with a process of validation carried out by the companions, which also counters criticisms from Western scholars regarding the qualifications of the companions in transmitting hadith. This research contributes to a deeper understanding of the development of hadith and the role of the companions in shaping the Islamic tradition and preserving the authentic teachings of Islam.